Architecture in medieval India: forms, contexts, histories - Juneja, Monica (Permanent Black, 2001)
Contributed articles
Collection of articles by various authors drawn from previously published sources. - Includes bibliographical references (p. [623]-640)
Keywords: Geschichte 1000-1700; Architektur; Indien; Geschichte 1000-1500